Testing the hypothesis of accelerated cerebral white matter aging in schizophrenia and major depression - Kochunov, P; Glahn, D; Rowland, L; Olvera, R; Winkler, A; Yang, Y; Sampath, H; Carpenter, W; Duggirala, R; Curran, J; Blangero, J; Hong, L (Elsevier, 2013)
Background: Elevated rate of aging-related biological and functional decline, termed “accelerated aging,” is reported in patients with schizophrenia (SCZ) and major depressive disorder (MDD). We used diffusion tensor imaging derived fractional anisotropy (FA) as a biomarker of aging-related decline in white matter (WM) integrity to test the hypotheses of accelerated aging in SCZ and MDD. Methods: The SCZ cohort comprised 58 SCZ patients and 60 controls (aged 20–60 years). The MDD cohort comprised 136 MDD patients and 351 controls (aged 20–79 years). The main outcome measures were the diagnosis-by-age interaction on whole-brain-averaged WM FA values and FA values from 12 major WM tracts. Results: Diagnosis-by-age interaction for the whole-brain average FA was significant for the SCZ (p = .04) but not the MDD (p = .80) cohort. Diagnosis-by-age interaction was nominally significant (p < .05) for five WM tracts for SCZ and for none of the tracts in the MDD cohort. Tract-specific heterochronicity of the onset of age-related decline in SCZ demonstrated strong negative correlations with the age-of-peak myelination and the rates of age-related decline obtained from normative sample (r = −.61 and −.80, p < .05, respectively). No such trends existed for MDD cohort. Conclusions: Cerebral WM showed accelerated aging in SCZ but not in MDD, suggesting some difference in the pathophysiology underlying their WM aging changes. Tract-specific heterochronicity of WM development modulated presentation of accelerated aging in SCZ: WM tracts that matured later in life appeared more sensitive to the pathophysiology of SCZ and demonstrated more susceptibility to disorder-related accelerated decline in FA values with age. This trend was not observed in MDD cohort.